2022
DOI: 10.3390/biomedicines10112758
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Bone Metastases on Patients with Renal Cell Carcinoma or Melanoma Treated with Combotherapy Ipilimumab Plus Nivolumab

Abstract: (1) Background: Ipilimumab plus nivolumab (combo-ICI) improves overall survival (OS) in patients with advanced renal cell carcinoma (RCC) or melanoma. The impact of bone metastases (BM) on survival outcomes of combo-ICI-treated patients is unknown. (2) Methods: This single-center retrospective observational study involved 36 combo-ICI-treated patients with advanced RCC and 35 with melanoma. Clinical and laboratory data preceding the initiation of combo-ICI were collected. Univariate and multivariate Cox propor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…A recent retrospective study of renal cell carcinoma (RCC) bone metastatic patients treated with ipi/nivo identified a relatively low response rate (21 %) and median OS (25.6 months) [57] , indicative of poor clinical outcome. Supporting these results, another study in advanced RCC found that patients with bone metastases receiving ipi/nivo had a lower 12-month OS rate (41.7 %) compared to patients without baseline bone metastases (82.7 %) treated with ipi/nivo [58] . Taken together, these studies suggest bone metastatic patients are less responsive to combination treatment with PD-1 and CTLA-4 inhibitors than non-bone metastatic patients.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…A recent retrospective study of renal cell carcinoma (RCC) bone metastatic patients treated with ipi/nivo identified a relatively low response rate (21 %) and median OS (25.6 months) [57] , indicative of poor clinical outcome. Supporting these results, another study in advanced RCC found that patients with bone metastases receiving ipi/nivo had a lower 12-month OS rate (41.7 %) compared to patients without baseline bone metastases (82.7 %) treated with ipi/nivo [58] . Taken together, these studies suggest bone metastatic patients are less responsive to combination treatment with PD-1 and CTLA-4 inhibitors than non-bone metastatic patients.…”
Section: Introductionmentioning
confidence: 73%
“…NSCLC = non-small cell lung cancer, RCC = renal cell carcinoma, OS = median overall survival, ICI = immune checkpoint inhibitor. Clinical Studies Cancer Type Treatment Number of Patients Outcome in patients with bone metastases *Compared to patients with no bone metastases P-Value Reference Non-squamous NSCLC Nivolumab 626 BoM+ 962 BoM- 7.9 month decrease in OS* p < 0.0001 [47] – Landi, et al, J Immunother Cancer , 2019 NSCLC Nivolumab 59 BoM+ 78 BoM- OS not achieved* p < 0.0001 [48] – Zhu, et al, Lung Cancer , 2022 Unspecified ICI 103 total 11.4 month decrease in OS* p = 0.0036 [52] – Li, et al, Thorac Cancer , 2020 Squamous NSCLC Nivolumab 120 BoM+ 251 BoM- 5.9 month decrease in OS* p < 0.0001 [47] – Landi, et al, J Immunother Cancer , 2019 Urothelial Unspecified ICI 86 BoM+ 122 BoM- 3.9 month decrease in OS* p = 0.005 [53] – Raggi, et al, Clin Genitourin Cancer , 2022 RCC Ipilimumab/Nivolumab 80 BoM+ 25.6 month OS (relatively low response rate) N/A [57] – Desai, Target Oncol , 2021 Ipilimumab/Nivolumab 9 BoM+ 27 BoM- 41% decrease in 12-month OS rate* p = 0.021 [58] – Pham, et al, Biomedicines , 2022 …”
Section: Introductionmentioning
confidence: 99%
“…Iinuma et al reported that pretreatment NLR was a prognostic factor for survival in RCC patients treated with NIVO +IPI [ 15 ]. In contrast, pretreatment NLR is not a significant predictor of response to NIVO + IPI therapy [ 16 , 17 ]. In our study, pretreatment NLR was not significantly associated with either PFS or OS; therefore, the utility of NLR in NIVO + IPI therapy remains controversial and must be further elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Based on their evidence to be associated with oncological outcomes of aRCC, the variables clear cell histology, International Metastatic Renal-Cell Carcinoma Database Consortium (IMDC) favorable prognosis group and neutrophil-tolymphocyte ratio (NLR) < 3 were compared with 1DC status to elucidate predictors for efficacy of ICI, i.e. addressing the primary outcome measure, by logistic regression analysis [17][18][19]. An additional exploratory analysis examined those cases, which had never received ICI treatment during sequential therapy.…”
Section: Discussionmentioning
confidence: 99%